1964
DOI: 10.1152/jappl.1964.19.4.653
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of respiratory flow resistance in man

Abstract: Measurements of flow resistance of various components of the respiratory system were measured in adult male subjects in the sitting position. Nasal resistance is the largest single component being nearly one-half the total and two-thirds of the airway resistance during nose breathing. It is highly nonlinear, and shows much variability. During mouth breathing upper airway resistance (mouth, pharynx, glottis, larynx and upper trachea) is also markedly nonlinear, and accounts for one-third the total airway resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
4
5

Year Published

1966
1966
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(174 citation statements)
references
References 0 publications
8
148
4
5
Order By: Relevance
“…31 The nasal passage contributes to approximately two-thirds of the upper airway resistance. 77 Any reduction in nasal airflow due to anatomic defects, such as nasal septal deviation or turbinate enlargement, can further increase this resistance, thereby increasing the likelihood of upper airway collapse during sleep and potentially worsening the severity of OSA. Additionally, anatomic defects can result in an increase in the required pressure during positive airway pressure therapy (eg, CPAP), the most commonly utilized treatment for this disorder.…”
Section: Supporting Textmentioning
confidence: 99%
“…31 The nasal passage contributes to approximately two-thirds of the upper airway resistance. 77 Any reduction in nasal airflow due to anatomic defects, such as nasal septal deviation or turbinate enlargement, can further increase this resistance, thereby increasing the likelihood of upper airway collapse during sleep and potentially worsening the severity of OSA. Additionally, anatomic defects can result in an increase in the required pressure during positive airway pressure therapy (eg, CPAP), the most commonly utilized treatment for this disorder.…”
Section: Supporting Textmentioning
confidence: 99%
“…There happens differences in the severity of the resistance in the airways depending on its localization as well [13]. The phasic airway response, occurring against the triggers like anxiety in healthy individuals, is generally thought to occur by the effects of upper airways (muscles of larynx, glottic aperature) more generally during expirium [17,20,21]. Ritz et al experimentally observed a total airway resistance against affective stimulants in healthy individuals only in the inspiratory section.8 However, in the experimental studies conducted afterwards, the inspiratory or the expiratory resistances in the airway that are created by affective stimulants could not have been proved to be superior to the other [19].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, airway resistance in a turbulent V ' regimen is proportional to gas density. It is considered that UA is characterized by a fully turbulent or a transitional V ' [10]. Therefore, the contribution of gas Table 1.…”
Section: Discussionmentioning
confidence: 99%